Feasibility and pharmacokinetics of caudal blockade in children and adolescents with 30–50 kg of body weight. Issue 11 (11th July 2016) - Keplinger, Maya; Marhofer, Peter; Klug, Wolfgang; Reiter, Birgit; Stimpfl, Thomas; Kettner, Stephan C.; Korf, Lena; Zeitlinger, Markus; Marhofer, Daniela; Triffterer, Lydia
Summary: Background: Caudal blockade, although an important technique of pediatric regional anesthesia, is rarely used in children heavier than 30 kg. This reservation is due to anatomical concerns and lack of pharmacokinetic data. We therefore set out to evaluate, in pediatric patients weighing 30−50 kg, the feasibility of ultrasound‐guided caudal blockade and the pharmacokinetics of caudally administered ropivacaine. Methods: Twenty consecutive children were included. General anesthesia was used to ensure a secured airway. For the caudal punctures, we applied the same clinical standards as in smaller children, administering ropivacaine 3.1 mg·ml ‐1 for a volume of 1 ml·kg −1 via ultrasound guidance. Pharmacokinetic analysis was based on total plasma ropivacaine levels and included maximum concentration ( C max ), time to C max ( t max ), terminal elimination half‐life, area under the concentration–time curve for the 4‐h sampling period, apparent total body clearance, and apparent volume of distribution. Results: In all 19 cases of successful puncture, we identified the relevant anatomical structures (sacral cornua, sacral hiatus, dura mater) and verified correct administration of the local anesthetic by visualizing its cranial spread. Surgical blockade was successful in 18 of 20 cases (90%; one puncture was technically not possible and one child received intraoperatively 50 μg fentanyl). The pharmacokinetic profile of the administered ropivacaine 3.1 mg·ml −1 indicated plasma levels within safe ranges in pediatric patients weighing 30−50 kg. Conclusions: Based on our pharmacodynamic and pharmacokinetic results, we suggest that the body weight of 50 kg it is feasible to perform effective and safe caudal blockade in children up to 50 kg body weight. Abstract :